2021
DOI: 10.1111/apps.12323
|View full text |Cite
|
Sign up to set email alerts
|

Complementary variable‐ and person‐centred approaches to the dimensionality of workaholism

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 96 publications
(225 reference statements)
4
21
1
Order By: Relevance
“…For both items, responses were provided on a 4‐point scale ranging from “Dissatisfied” to “Satisfied.” Importantly, prior research has established the relevance, reliability, and validity of single‐item measures of job and life satisfaction (similar and identical to those used in this study), which also have the advantage of being easier and quicker to complete, while retaining face validity (Fisher et al., 2016; Wanous et al., 1997). Likewise, additional studies have also supported the validity of similar single‐item measures of job and life satisfaction in relation to various measures of individual and contextual characteristics (e.g., Beutell, 2010; Gillet et al., 2022).…”
Section: Methodsmentioning
confidence: 90%
“…For both items, responses were provided on a 4‐point scale ranging from “Dissatisfied” to “Satisfied.” Importantly, prior research has established the relevance, reliability, and validity of single‐item measures of job and life satisfaction (similar and identical to those used in this study), which also have the advantage of being easier and quicker to complete, while retaining face validity (Fisher et al., 2016; Wanous et al., 1997). Likewise, additional studies have also supported the validity of similar single‐item measures of job and life satisfaction in relation to various measures of individual and contextual characteristics (e.g., Beutell, 2010; Gillet et al., 2022).…”
Section: Methodsmentioning
confidence: 90%
“…Overall, we acknowledge the lack of objective indicators as another limitation of our study, partially due to the self-reported nature of the investigated phenomena and the heterogeneity of included occupations. Although the temporal separation between workaholism and hedonic tone measurement likely reduced the risk of common method bias (see Beal, 2015), future studies should attempt to corroborate our findings with multimethod approaches while also including additional job demands and outcome variables and considering alternative operationalizations of workaholism (Clark et al, 2020;Gillet et al, 2022). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Limitations and Implicationsmentioning
confidence: 79%
“…Particularly, the meta-analysis by Clark et al (2016) confirmed the pattern of weak-to-moderate positive relationships between workaholism and work enjoyment but also highlighted negative relationships with job satisfaction, positive relationships with negative affect, and no significant association with positive affect. A controversial relationship between workaholism and job satisfaction has been also highlighted by more recent studies reporting negative (Gillet et al, 2022; Huyghebaert-Zouaghi et al, 2023) or mixed associations between the two constructs (Dordoni et al, 2019). Moreover, similar mixed results emerged from research focusing on obsessive work passion, a construct closely related to workaholism (see Williamson Smith et al, 2023) that was found both negatively (Horwood et al, 2021) and positively related to job satisfaction (Vergauwe et al, 2022).…”
Section: Affective Characterization Of Workaholismmentioning
confidence: 96%
“…Organisational support in the form of supervisor support, rewards, and favourable working conditions are vital to stimulating organisation-related outcomes, that is, reduced withdrawal behaviours and commitment ( Rhoades and Eisenberger, 2002 ; Gillet et al, 2022 ). Supervisor support is critical to replenish employee physical and psychological resources to increase their retention probability ( Kalliath and Kalliath, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%